2009
DOI: 10.1080/13647830903324186
|View full text |Cite
|
Sign up to set email alerts
|

Mode selection in weakly unstable two-dimensional detonations

Abstract: A formulation of the reactive Euler equations in the shock-attached frame is used to study the two-dimensional instability of weakly unstable detonation through direct numerical simulation. The results are shown to agree with the predictions of linear stability analysis. Comparisons are made with linear perturbation growth rates and oscillation frequencies as a function of transverse disturbance wavelength. The perturbation eigenfunctions predicted by linear stability analysis are directly validated through nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…It is nevertheless found that an equivalent resolution of 32 pts/l 1/2 is sufficient for the mixture and flow conditions used in the present study of unstable oblique detonation and hence, this resolution is used in all later simulations. Results using this same degree of resolution have also been reported in recent normal detonation studies [24,18]. Oblique detonations are overdriven, so on the direction vertical to the surface, there are fewer grids in half reaction length.…”
Section: Resolution Studysupporting
confidence: 58%
“…It is nevertheless found that an equivalent resolution of 32 pts/l 1/2 is sufficient for the mixture and flow conditions used in the present study of unstable oblique detonation and hence, this resolution is used in all later simulations. Results using this same degree of resolution have also been reported in recent normal detonation studies [24,18]. Oblique detonations are overdriven, so on the direction vertical to the surface, there are fewer grids in half reaction length.…”
Section: Resolution Studysupporting
confidence: 58%
“…However, it should not be concluded that this level of resolution is sufficient for obtaining quantitative values and suitable for all unstable detonation simulations. For cases with highly irregular detonation cells and for numerical studies aiming to predict the correct quantitative value of the growth rate, frequencies, cell spacing, stability boundary, etc., much higher resolutions are likely to be required (Short & Stewart 1998;Sharpe & Falle 2000a;Sharpe & Quirk 2008;Taylor, Kasimov & Stewart 2009). In fact, for very unstable detonations with highly irregular structure, the notion of 'grids per reaction zone length', i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Previous researchers use the grid number in half reaction length to evaluate the resolution of detonation simulations, and in recent studies the resolution of 32 grids half reaction length is usually used [22,23]. Unfortunately, we use the detailed reaction mechanism, which is hard to give the half reaction length because there is no ''reaction progress'' in these mechanisms.…”
Section: Initiation and Structures With Ma 70mentioning
confidence: 99%